3D printed PCLA scaffold with nano‐hydroxyapatite coating doped green tea EGCG promotes bone growth and inhibits multidrug‐resistant bacteria colonization. Issue 10 (5th July 2022) - Zhang, Xiangchun; He, Jian; Qiao, Liang; Wang, Ziqi; Zheng, Qinqin; Xiong, Chengdong; Yang, Hui; Li, Kainan; Lu, Chengyin; Li, Sanqiang; Chen, Hongping; Hu, Xulin
Abstract: Objectives: 3D‐printing scaffold with specifically customized and biomimetic structures gained significant recent attention in tissue engineering for the regeneration of damaged bone tissues. However, constructed scaffolds that simultaneously promote bone regeneration and in situ inhibit bacterial proliferation remains a great challenge. This study aimed to design a bone repair scaffold with in situ antibacterial functions. Materials and Methods: Herein, a general strategy is developed by using epigallocatechin‐3‐gallate (EGCG), a major green tea polyphenol, firmly anchored in the nano‐hydroxyapatite (HA) and coating the 3D printed polymerization of caprolactone and lactide (PCLA) scaffold. Then, we evaluated the stability, mechanical properties, water absorption, biocompatibility, and in vitro antibacterial and osteocyte inductive ability of the scaffolds. Results: The coated scaffold exhibit excellent activity in simultaneously stimulating osteogenic differentiation and in situ resisting methicillin‐resistant Staphylococcus aureus colonization in a bone repair environment without antibiotics. Meanwhile, the prepared 3D scaffold has certain mechanical properties (39.3 ± 3.2 MPa), and the applied coating provides the scaffold with remarkable cell adhesion and osteogenic conductivity. Conclusion: This study demonstrates that EGCG self‐assembled HA coating on PCLA surface could effectively enhance the scaffold's water absorption, osteogenic induction, and antibacterial properties in situ. It provides a new strategy to construct superior performance 3D printed scaffold to promote bone tissue regeneration and combat postoperative infection in situ. Abstract : Schematic diagram of the 3D polymerization of caprolactone and lactide (PCLA) coated scaffold containing epigallocatechin‐3‐gallate (EGCG)‐modified nano‐HA as an artificial bone matrix with biphasic function to efficiently promote the growth of osteoblasts and inhibit methicillin‐resistant Staphylococcus aureus colonization in the bone repair microenvironment. PCLA/KH‐HA‐EGCG exhibited satisfactory antibacterial properties and leads to significant osteoinduction and osteogenic differentiation in osteoblasts cells, achieving a high‐efficient bone repair effect.